2022
DOI: 10.31234/osf.io/exruk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparing Psychopathy Across Measurement Modalities

Abstract: Psychopathy is a collection of personality traits and behaviors that are associated with costly personal, interpersonal, and societal outcomes. The nature of this construct has been widely debated across decades of literature and such debates have produced a multitude of instruments for the measurement of psychopathy. These measures include self-reports and clinical interviews, yet little work has examined the degree to which measurements of psychopathy may differ across these modalities and whether such poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Such analyses have facilitated critical advances in various domains of psychological research (e.g., Robinaugh et al, 2020). For example, network studies have revealed important psychometric differences in the modality of assessment used for forms of psychopathology commonly linked with violent behavior (e.g., psychopathy; West, Psederska, et al, 2022) and the theoretical structure of aggressive and antagonistic personality traits (e.g., . PNA has similarly been used to identify targets for clinical intervention.…”
Section: Known Warning Signsmentioning
confidence: 99%
“…Such analyses have facilitated critical advances in various domains of psychological research (e.g., Robinaugh et al, 2020). For example, network studies have revealed important psychometric differences in the modality of assessment used for forms of psychopathology commonly linked with violent behavior (e.g., psychopathy; West, Psederska, et al, 2022) and the theoretical structure of aggressive and antagonistic personality traits (e.g., . PNA has similarly been used to identify targets for clinical intervention.…”
Section: Known Warning Signsmentioning
confidence: 99%